Challenges and Solutions to the Recurrent Measles Outbreak in Somalia - Tahlil, Abdullahi Ahmed; Mohamed, Mohamed Abdelrahman; Osman, Marian Muse; Gedi, Saido; Ali, Bisma; Muhumed, Mukhtar Bulale; Ahmed, Abdirahman Abdirizak (Somali Health Action Journal, 2024)
This study aims to address the persistent challenge of recurrent measles outbreaks in Somalia by providing an analysis of underlying issues and proposing evidence-based solutions. Measles, a highly contagious viral infection, continues to pose significant threat to public health worldwide, with Somalia facing unique challenges due to its complex geographical and sociopolitical landscape. The country’s history of conflict, fragile healthcare infrastructure, and limited access to basic healthcare services have hindered efforts to control preventable diseases like measles. These recurrent outbreaks do not only have immediate consequences on public health but also exacerbate an already precarious situation in Somalia, leading to substantial socioeconomic impacts as families grapple with the dual burden of disease and strain on livelihoods. The primary objective of this communication is to analyze the challenges contributing to the persistence of measles outbreaks in Somalia and propose evidencebased solutions. To achieve this goal, the subsequent sections of this brief delve into the specific challenges facing Somalia in its battle against recurrent measles outbreaks. These challenges encompass issues such as vaccine access, vaccine hesitancy, coverage disparities, fragility of healthcare infrastructure, obstacles in community engagement, and limitations in disease surveillance and response. Understanding these intricate factors is crucial for designing targeted interventions that not only mitigate the immediate impact of measles outbreaks but also establish a foundation for long-term prevention.